2022
DOI: 10.1177/02611929221121076
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in Non-Technical Project Summaries to Promote the Three Rs in Respiratory Disease Research

Abstract: Non-Technical Project Summaries (NTS) are legal documents that were first introduced by the Directive 2010/63/EU to enhance transparency within scientific animal experimentation. Researchers intending to conduct biological research on animal models must fulfil the NTS requirements by outlining their proposed use of animals and how they plan to implement the Three Rs (replacement, reduction and refinement of animal use) in their experiments. This study outlines a novel systematic analysis approach that enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Finally, another positive message comes out in the article analysing the Non-Technical Project Summaries (NTS) submitted in the UK between the years 2013–2020, in which Bonaserra et al 5 have shown that improved completion of the NTS by researchers can promote the implementation of non-animal alternatives in fields where this is currently lacking, such as respiratory disease research. It is a very positive finding that, after the introduction of Regulation 2019/1010 EU , the transparency level increased significantly due to the adoption of a new reporting template.…”
mentioning
confidence: 99%
“…Finally, another positive message comes out in the article analysing the Non-Technical Project Summaries (NTS) submitted in the UK between the years 2013–2020, in which Bonaserra et al 5 have shown that improved completion of the NTS by researchers can promote the implementation of non-animal alternatives in fields where this is currently lacking, such as respiratory disease research. It is a very positive finding that, after the introduction of Regulation 2019/1010 EU , the transparency level increased significantly due to the adoption of a new reporting template.…”
mentioning
confidence: 99%